Géologie, théologie et inquiétudes eschatologiques : William Thomson (Lord Kelvin) et les débats suscités par la thermodynamique à l’époque victorienne - Jean-Michel Yvard (Cahiers Victoriens et Edouardiens, 2010)
William Thomson (1824-1907), an eminent physicist who contributed to the formulation of the second law of thermodynamics, was also at the origin of a largely forgotten controversy concerning the ages of the Sun and the Earth. He used the laws of thermodynamics to calculate the age of our planet and he concluded that it was probably from 100 to 500 million years old, which was much lower than the estimations currently accepted by geologists, and threatened to put into question the darwinian theory of evolution. Moreover, thermodynamics did not only announce a gradual exhaustion of the resources of the Sun or of our planet, but also the heat death of the universe as a whole. This paper explores the uncertainties and the debates which were caused by such conceptions, which were also used, in a more imaginative way, by H. G. Wells in his famous novel The Time Machine.